2010
DOI: 10.1007/s00436-010-1818-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antileishmanial activity from marine sponge extracts collected off the Tunisian coast

Abstract: The present study reports on the in vitro antileishmanial activity of two Ircinidae (Dictyoceratida, Demospongiae, Porifera) Ircinia spinosula and Sarcotragus sp. Sampled from the east coast of Tunisia. The ethyl acetate, dichloromethane, and aqueous extracts were tested against Leishmania major promastigotes. The anti-proliferative activity was checked using different extracts concentration during 72 h. We found that the IC50 (sub-inhibitory concentration) values ranged from 1.39 to 264.67 mug/ml. The most ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…known as Tunisian sponge prepared in dichloromethane has demonstrated in-vitro anti-leishmanial activity by demonstrating the associated morphological alterations in promastigotes of leishmania major. [ 16 ]…”
Section: Classification Of Marine Pharmacologymentioning
confidence: 99%
“…known as Tunisian sponge prepared in dichloromethane has demonstrated in-vitro anti-leishmanial activity by demonstrating the associated morphological alterations in promastigotes of leishmania major. [ 16 ]…”
Section: Classification Of Marine Pharmacologymentioning
confidence: 99%
“…; Ben Kahla‐Nakbi et al . ). The only reports concerning the reproduction of S. spinosulus are those of Carballo et al .…”
Section: Introductionmentioning
confidence: 97%
“…Members of the order Dictyoceratida are viviparous and the incubated larvae are parenchymellae (Cook & Bergquist 2002). Although there are several reports of the demosponge S. spinosulus worldwide, the majority of the research deals with the antibacterial, cytotoxic and antifouling activities of the metabolites extracted from this species (De Rosa et al 1995;Mihopoulos et al 1999;Tsoukatou et al 2002;Liu et al 2006;Ben Kahla-Nakbi et al 2010). The only reports concerning the reproduction of S. spinosulus are those of Carballo et al (1994), who observed the presence of specimens in reproduction in November, and of Scalera Liaci et al (1971), who noticed that the only specimen examined (cited as Ircinia spinosula) in February showed oocytes ranging from 40 to 190 lm.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the etiologic agent of visceral leishmaniasis in Brazil, the L. (L.) chagasi, was the most resistant specie. Differences in drug susceptibility have been shown among Leishmania parasites, including isolated compounds from plants (Velozo et al 2006;Santin et al 2009;Sartorelli et al 2009;Sharma et al 2009;Grecco et al 2010;Guimarães et al 2010;Kahla-Nakbi et al 2010;Corrêa et al 2011;Duran et al 2011;Ghosh et al 2011). In the test with the clinical relevant form of L. (L.) chagasi, the lack of selectivity toward amastigotes could be described to the higher metabolic resistance, a natural consequence of adaptative response to the hazardous intracellular milieu of macrophages.…”
Section: Discussionmentioning
confidence: 98%